Studi Kasus Kemudahan Sistem Kearsipan Elektronik Berbasis Aplikasi Srikandi pada Lingkup Biro Umum Kementerian Hukum Republik Indonesia - Alfaaflahah Alfaaflahah; Marsofiyati Marsofiyati; Maulana Amirul Adha (Indo Publishing, 2026)
This study aims to examine the ease of using the electronic archives system based on the SRIKANDI application within the scope of the General Bureau of the Ministry of Law of the Republic of Indonesia. This research employs a qualitative approach with a descriptive case study method. Data were collected through observation, in-depth interviews, and documentation with employees directly involved in digital administrative management using the SRIKANDI application. Data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing. The application of triangulation techniques ensured the validity and credibility of the data. The results indicate that the SRIKANDI application makes a positive contribution to improving administrative process efficiency, such as accelerating document distribution, enhancing transparency, facilitating archive retrieval, and supporting digital coordination. However, its implementation has not been fully optimal due to several obstacles, including unstable internet connections, system disruptions during working hours caused by high user volumes, and limited digital competence among some employees. This research is expected to serve as evaluative material for developing more effective and optimal electronic archive systems within government institutions.